Dyspnea after pulmonary embolism: a nation‐wide population‐based case–control study. (1st September 2021) - Nilsson, Lars T.; Andersson, Therese; Larsen, Flemming; Lang, Irene M.; Liv, Per; Söderberg, Stefan
Abstract : Dyspnea is common after a pulmonary embolism. Often, but not always, the dyspnea can be explained by pre‐existing comorbidities, and only rarely by chronic thromboembolic pulmonary hypertension (CTEPH). CTEPH is probably the extreme manifestation of a far more common condition, called the post‐pulmonary embolism syndrome. The purpose of this retrospective study was to investigate the prevalence and predictors of dyspnea among Swedish patients that survived a pulmonary embolism, compared to the general population. All Swedish patients diagnosed with an acute pulmonary embolism in 2005 (n = 5793) were identified via the Swedish National Patient Registry. Patients that lived until 2007 (n = 3510) were invited to participate. Of these, 2105 patients responded to a questionnaire about dyspnea and comorbidities. Data from the general population (n = 1905) were acquired from the multinational MONItoring of trends and determinants in CArdiovascular disease health survey, conducted in 2004. Patients with pulmonary embolism had substantially higher prevalences of both exertional dyspnea (53.0% vs. 17.3%, odds ratio (OR): 5.40, 95% confidence intervals (CI): 4.61–6.32) and wake‐up dyspnea (12.0% vs. 1.7%, OR: 7.7, 95% CI: 5.28–11.23) compared to control subjects. These differences remained after adjustments and were most pronounced among younger patients. The increased risk for exertional dyspnea and wake‐up dyspnea remained after propensity score matching (OR (95% CI): 4.11 (3.14–5.38) and 3.44 (1.95–6.06), respectively). This population‐based, nation‐wide study demonstrated that self‐reported dyspnea was common among patients with previous pulmonary embolism. This finding suggested that a post‐pulmonary embolism syndrome might be present, which merits further investigation.